State of the UK Climate 2019. (30th July 2020) - Kendon, Mike; McCarthy, Mark; Jevrejeva, Svetlana; Matthews, Andrew; Sparks, Tim; Garforth, Judith
INTRODUCTION: This report provides a summary of the UK weather and climate through the calendar year 2019, alongside the historical context for a number of essential climate variables. This is the sixth in a series of annual 'State of the UK Climate' publications and an update to the 2018 report (Kendon et al ., 2019). It provides an accessible, authoritative and up‐to‐date assessment of UK climate trends, variations and extremes based on the most up to date observational datasets of climate quality. The majority of this report is based on observations of temperature, precipitation, sunshine and wind speed from the UK land weather station network as managed by the Met Office and a number of key partners and co‐operating volunteers. The observations are carefully managed such that they conform to current best practice observational standards as defined by the World Meteorological Organization (WMO). The observations also pass through a range of quality assurance procedures at the Met Office before application for climate monitoring. Time series of near‐coast sea‐surface temperature (SST) and sea‐level are also presented and in addition a short section on phenology which provides dates of first leaf and bare tree indicators for four common shrub or tree species. National and regional statistics in this report are from the HadUK‐Grid dataset (Hollis et al ., 2019). Temperature and rainfall series from this dataset extend back to 1884 and 1862, respectively. Details are provided in the relevant sections and appendices. The report presents summary statistics for the year 2019 and the most recent decade (2010–2019) relative to 1961–1990 and 1981–2010 averages. The period 2010–2019 is a non‐standard reference period, but it provides a 10‐year 'snapshot' of the most recent experience of the UK's climate and how that compares to historical records. This means differences between 2010 and 2019 and the baseline reference averages may reflect shorter‐term decadal variations as well as long‐term trends. These data are presented to show what has happened in recent years, not necessarily what is expected to happen in a changing climate. The majority of maps in this report show the year 2019 relative to the 1981–2010 baseline reference averaging period—that is, they are anomaly maps which show the spatial variation in this difference from average. Maps of actual values are in most cases not displayed because these are dominated by the underlying climatology, which for this report is of a lesser interest than the year‐to‐year variability. Throughout the report's text the terms 'above normal' and 'above average', and so on refer to the 1981–2010 baseline reference averaging period unless otherwise stated. Values quoted in tables throughout this report are rounded, but where the difference between two such values is quoted in the text (e.g., comparing the most recent decade with 1981–2010), this difference is calculated from the original unrounded values. Updates compared to State of UK Climate 2018 A section on phenology has been added The method used to calculate rainfall percentiles (fig. 31) has been revised Updated climate data to HadUK‐Grid version 1.0.2.0, including data rescue projects that have improved or extended early monthly sunshine and rainfall series. Feedback We would welcome suggestions or recommendations for future publications of this report. Please send any feedback to the Met Office at ncic@metoffice.gov.uk This State of the UK Climate report was supported by the Met Office Hadley Centre Climate Programme funded by BEIS and Defra. Abstract :